KINERJA KEUANGAN PERUSAHAAN ASURANSI SYARIAH DI INDONESIA: SURPLUS ON CONTRIBUTION - Ai Fitri Nurlatifah; Sepky Mardian (Department of Accounting-Faculty of Economic and Business (FEB), 2016)
This study aims to identify the impact of size, leverage, liquidity, tangibility, volume of capital and loss ratio on the financial performance of Sharia Insurance Companies in Indonesia as measured by Surplus On Contribution (SOC) from 2012 to 2014. The data analysis technique used is panel data regression with a significance level of 5% (0.05). Results of the data analysis showed that the right model used in this study is the Fixed Effects Model (FEM). Simultaneously the six variables significantly influence the good financial performance as measured by SOC. Partially; the size (0.0000) has a positive influence on the financial performance (SOC), whereas leverage (0.0167) and volume of capital (0.0000) negatively affect performance finance (SOC). Liquidity variable (0.8552), tangibility (0.5513) and loss Ratio (0.9861) did not have a significant effect on the financial performance (SOC).DOI: 10.15408/akt.v9i1.3590